Toxic Effects Observed on Light Weight Proteins of Musca domestica with Pb(CH3COO)2 - Rizwanul Haq,; Ehteshamul Haq ,; M. Farhanullah Khan, (Journal of Basic & Applied Sciences, 2021)
Lead is considered to be an important noxious waste which could contaminate the environment, such as soil, air and water, therefore, insects could be influenced easily by the lead. Musca domestica, was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations. It was observed that under the effects of lead abnormalities and deformity were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards due to lead contamination, which exerts a specific physiological and morphological effect on these flies.